[Interviews about the location of the Museum of Ethnography, Budapest]
Contains interviews related to the issue of moving the Museum of Ethnography of Budapest in a different place in order to make space for one of the Ministries of Budapest in Kossuth Lajos tér (square) where the Parliament of Hungary is located. Among the interviewees, key speakers are Fejér Zoltán (Director of Museum of Ethnography of Budapest), László Visy (State Secretary, Hungarian Ministry of Cultural Heritage) and Gábor Borókai (spokesman of the Hungarian government).